Acidic Deep Eutectic Solvents as Active Media for Sustainable Synthesis of Biindoles Starting from 2, 2'‐Diaminotolanes and Aldehydes. Issue 16 (4th April 2023) - Brambilla, Elisa; Gritti, Alessandra; Pirovano, Valentina; Arcadi, Antonio; Germani, Raimondo; Tiecco, Matteo; Abbiati, Giorgio
Abstract: We describe an alternative and more sustainable method for the synthesis of 2, 2'‐disubstituted 3, 3'‐biindoles starting from 2, 2'‐diaminotolanes and (hetero)arylaldehydes. The key feature of the approach is the use of an acidic Deep Eutectic Solvent (DES) able to exploit a double activity, i. e., solvent and Brønsted Acid (BA) catalyst, avoiding the use of Volatile Organic Compounds (VOCs) as solvents and additional acid catalysts. By this way, we synthesized twenty‐five biindoles, including eighteen new compounds. The reactions run quickly under mild conditions by microwave heating at 70 °C, with yields ranging from good to very good. The reaction scope is rather broad. The medium demonstrated to be reusable at least five times with only a slight reduction in yields. Based on experimental evidence and previous literature findings, a plausible mechanism is proposed. Abstract : The use of an "active" acidic Deep Eutectic Solvent (DES) as solvent/catalyst together with dielectric heating promote a more sustainable preparation of biindoles through a tricky cascade cyclization process starting from 2, 2'‐diaminotolanes and (hetero)arylaldehydes.